Unconventional monetary policy and funding liquidity risk - Adrien d'Avernas; Quentin Vandeweyer; Matthieu Darracq Pariès (European Central Bank (ECB), 2020)
This paper investigates the efficiency of various monetary policy instruments to stabilize asset prices in a liquidity crisis. We propose a macro-finance model featuring both traditional and shadow banks subject to funding risk. When banks are well capitalized, they have access to money markets and efficiently mitigate funding shocks. When aggregate bank capital is low, a vicious cycle arises between declining asset prices and funding risks. The central bank can partially counter these dynamics. Increasing the supply of reserves reduces liquidity risk in the traditional banking sector, but fails to reach the shadow banking sector. When the shadow banking sector is large, as in the US in 2008, the central bank can further stabilize asset prices by directly purchasing illiquid securities.
Keywords: E43; E44; E52; G12; 330; Asset Pricing; Quantitative Easing; Money Markets; Shadow Banks